The Effect of Seed Priming with Salicylic Acid and Ascorbic Acid on Viability of Local Okra (Abelmoschus Esculentus L.) Seeds Stored for Three Years - Hussein J. Hussein (Journal of Global Pharma Technology, 2017)
The present study was conducted to knowledge the effect of seed priming techniques on seeds viability characteristics of okra seeds, an experiment were conducted at the seeds obtained directly from the okra field of Babil governorate during the season of (2012) and stored until 2015. Seeds were treated for 6 hours at 30 Cº with priming media (50mg/L of ascorbic acid, 100mg/L of salicylic acid, hydro-priming and untreated seeds as control).Maximum seed germination percentage, germination index (GI), seedling vigour index (SVI), root length, shoot length, seedling length, seedling fresh and dry weights were observed when the seeds treated with (100 mg/L of salicylic acid and 50 mg/L of ascorbic acid) compared with control.Keywords: Seed priming, Ascorbic Acid, Salicylic acid, Okra seeds.